The Role of Ethics and the Educational Profession in Character Education - Pratiwi, Anggi; Dwi Zahra, Febri (International Journal of Students Education, 2023)
This article discusses the important role of ethics and the educational profession in character education. Ethics, which includes moral principles that regulate individual actions and behavior, and the educational profession, which involves the teacher’s responsibility in forming students’ character, are important factors in forming moral and responsible individuals. Character education plays a crucial role in forming a young generation who has integrity, responsibility, and is able to contribute positively to society. In the midst of challenges and changes that continue to occur in the world, it is important for us to look at the role of ethics and the educational profession in character education. Ethics and the educational profession have a close relationship and are interrelated in developing student character. Ethics in the educational profession is a set of moral values and principles held by educators. This includes the moral obligations that educators have in carrying out their duties in teaching and forming student character. Ethics in education involves ethics and moral behavior, as well as norms that educators must adhere to in carrying out their dutiesIn character education, teachers act as role models who practice moral values in everyday life and teach them consistently to students. The education profession provides guidance for teachers in integrating character learning into the curriculum and creating a positive educational environment.